Mundo da música: Card Game - Stocchero, Lucas (2011)
This Project consists in a research about card and board games. Discuss game production and developing concepts, such as their rules, illustrations and layouts. With a package and booklet study. Brings as result 37 card layouts, package, rules booklet, configuring a completed product. Topics as brand, backgrounds, textures, and production and image valorization techniques are briefly addressed. These topics are considered too important for not being quoted, although they are not the focus of this project.